2016
DOI: 10.4062/biomolther.2016.008
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin Induces Apoptotic Cell Death via Regulation of p53 and Nrf2 in AGS Human Stomach Carcinoma Cells

Abstract: Shikonin, which derives from Lithospermum erythrorhizon, has been traditionally used against a variety of diseases, including cancer, in Eastern Asia. Here we determined that shikonin inhibits proliferation of gastric cancer cells by inducing apoptosis. Shikonin’s biological activity was validated by observing cell viability, caspase 3 activity, reactive oxygen species (ROS) generation, and apoptotic marker expressions in AGS stomach cancer cells. The concentration range of shikonin was 35–250 nM with the incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The up-regulation of p73 and down-regulation of ICBP90 during the shikonin treatment also led to the apoptosis of human cancer cells [20]. Shikonin could induce apoptosis, necrosis by up-regulating p53 and Nrf2 expression in lung cancer and stomach carcinoma [21, 22]. Therefore, to study the effect of shikonin on the CCA cells is significant for the new method of clinical therapy in CCA.…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulation of p73 and down-regulation of ICBP90 during the shikonin treatment also led to the apoptosis of human cancer cells [20]. Shikonin could induce apoptosis, necrosis by up-regulating p53 and Nrf2 expression in lung cancer and stomach carcinoma [21, 22]. Therefore, to study the effect of shikonin on the CCA cells is significant for the new method of clinical therapy in CCA.…”
Section: Introductionmentioning
confidence: 99%
“…Natural anticancer compounds inhibit tumor growth and progression by reducing cell migration, invasion, and metastasis [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Interestingly, chalcone-like chain CTI-82 exhibits several pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies 21 - 23 have found shikonin had antitumor effect in various cancer types, the mechanisms of which were given on the aspects of induction of apoptosis, necrosis, acting on proteasome, protein tyrosine kinase and anti-angiogenesis. The molecular mechanisms mainly included stimulating ROS generation 22 in the mitochondria, inhibiting the activities of DNA topoisomerases, increasing expression of p53 23 , 24 and inhibition of cancer cell glycolysis via targeting PKM2, polo-like kinase1 (PLK1) and protein tyrosine kinase (PTK) 19 , 25 . Compared with previous studies, our study found that shikonin inhibited HIF1α/pkm2/CyclinD1 signal pathway to regulate the proliferation of esophageal cancer cells.…”
Section: Discussionmentioning
confidence: 99%